Top 100 most-cited articles on pediatric anesthesia from 1990 to 2023 - Kai Zhang; Yue Jin; Jia Zhong; Wenyuan Zhang; Minyue Qian; Zhongteng Lu (BMJ Publishing Group, 2024)
Pediatric anesthesia presents greater challenges than does adult anesthesia. This bibliometric analysis aimed to analyze the top 100 most cited articles to be better understand the hot spots and prospects in pediatric anesthesia. Articles and reviews related to pediatric anesthesia were retrieved from the Web of Science Core Collection from 1990 to 2023. A bibliometric analysis of the top 100 most cited articles was also performed using information such as topics, author names, countries, institutions, publication years, and journals. A total of 32 831 articles were identified, with a total of 32 230 citations for the top 100 articles. The peak period for pediatric anesthesia research was from 2005 to 2009. The USA has emerged as the most active country in pediatric anesthesia research. Major journals published included Anesthesia and Analgesia, Anesthesiology, and Pediatrics, underscoring their authority in the field. Clinical studies on the top 100 most cited articles have focused on different stages of the perioperative period, the use of different anesthetic agents, and adverse outcomes in pediatric patients. The current study conducted a bibliometric analysis of the top 100 most cited articles in the field of pediatric anesthesia. Such insights are valuable for identifying research hot spots, assessing academic impact and collaboration in pediatric anesthesia, and guiding future research directions.